Silent Stress of Infertility Suffering Nepalese Couple: A Study of Urban and Rural Areas - Kabita Khatiwada, (Journal of Balkumari College, 2025)
Infertility is a silent phenomena which no one wish to disclose in society because this is stressful to the couple. This study aim to find out the infertility and societal perspectives and action taken among the couple of Bharatpur Rural and Urban areas of Nepal. A case study example of some 16 couples through phone interview generates many evidences and facts that helps to generalize the fact of infertility and its societal effects are one of the mixed method of this study. Study were conducted during Feb-March 2025. The study found that the couples are highly suffering of mental, domestic and societal stress not being conceived. The rate of shame, low mentality and moral are highly affected due to the infertility. The stress also effects on the quality of work doing in the home and outside. The societal view in rural sectors is more vibrant and communicable compared to the urban areas with low sharing. Alternative fertility mechanism are the best mode to conceive and child birth, this process much helpful to the couples start cover there all backlogs’. Study concluded that infertility word is enough to exaggerate stress level that downsize the level of quality of work and thoughts.